Pareidolia: characterising facial anthropomorphism and its implications for product design. (2018) - Wodehouse, Andrew; Brisco, Ross; Broussard, Ed; Duffy, Alex
This work highlights the phenomenon of pareidolia - the tendency to see faces in the environment, buildings and objects that surround us - and establishes its relevance for design contexts. In reviewing literature on anthropomorphism and the use of faces in design embodiment, we have shown that it is a compelling and prevalent facet of how we interpret products. By surveying 2, 309 images from across the internet, we provide the first systematic investigation of product types and face characteristics (size, composition, emotion) that are manifest in this phenomenon. The most common instances were shown to be in medium-sized products, where part of the product was interpreted as a face, and that conveyed a happy emotion. The effects of culture and self-congruence are identified as important aspects of our interpretation of facial emotion. It is concluded that the fundamental geometric elements of products should be considered with respect to facial morphology, whether it be the intention to utilise its effects or not, and set out the case for more quantified guidelines on the use of pareidolia and anthropomorphism in design.